PERLINDUNGAN HUKUM TERHADAP NASABAH BANK DALAM PENGGUNAAN KARTU ATM DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Hirwansyah; Dwi Atmoko (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
The increasing development of technology has had a very significant impact in the financial sector. In the banking sector, of course it has a fundamental impact. The use of technology with digital transactions, especially using Automatic Teller Machines (ATMs), has its own value for bank customers. The use of ATMs by customers cannot be separated from the negative or positive value of the ATM. In fact, basically using an ATM is easier and saves time and energy. However, in implementation, failures sometimes occur which in the end will only harm bank customers, in this case consumers. As is known, bank customers themselves are also consumers, regulated in Law Number 8 of 1999 concerning Consumer Protection. Losses received by bank customers. Not necessarily because of the customer's own negligence, but also because of the failure of the ATM system. Sometimes the bank does not want to compensate for losses due to this incident, saying that it was due to customer negligence. The Customer Service System implemented by the Bank, in this case benefiting the bank, is of course detrimental to consumers. For this reason, it is necessary to have special regulations that regulate the role of banks in providing services to customers so that each party has the same rights and obligations in becoming partners, in this case between the bank and its customers.